Characterization of biomimetic silicate- and strontium-containing hydroxyapatite microparticles embedded in biodegradable electrospun polycaprolactone scaffolds for bone regeneration; European Polymer Journal; Vol. 113 - Surmenev R. A. Roman Anatolievich; Shkarina S. N. Svetlana Nikolaevna; Syromotina D. S. Dina Sergeevna; Melnik E. V. Elizaveta Vasilievna; Selezneva I. I. Irina Ivanovna; Ermakov A. M. Artem Mihailovich; Ivlev S. I. Sergei; Cecilia A. Angelica; Weinhardt V. Venera; Baumbach T. Tilo; Rijavec T. Tomaz; Lapanje A. Ales; et al. (2019, 2019)
Title screen